Law and Development in Latin America - Karst, Kenneth L.; Rosenn, Keith S. (Berkeley, CA : University of California Press, 2020)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1975.
Frontmatter -- PREFACE -- CONTENTS -- TABLE OF CASES -- LIST OF FOREIGN ABBREVIATIONS -- INTRODUCTION -- Chapter I. HISTORICAL DEVELOPMENT OF LATIN AMERICAN LEGAL INSTITUTIONS -- Chapter II. ROLE OF THE COURTS IN CONTROLLING GOVERNMENTAL ACTION -- Chapter III. LAND REFORM -- Chapter IV. LAW AND INFLATION -- Chapter V. LEGAL INSTITUTIONS IN THE CARACAS BARRIOS: A LAW-IN-SOCIETY CASE STUDY -- Chapter VI. PERSPECTIVES ON LAW AND DEVELOPMENT -- APPENDIX A. BRAZIL: STATUTE REGULATING THE WRIT OF SECURITY -- APPENDIX B. MEXICO: CONSTITUTION OF 1917 (AS AMENDED, 1968) -- APPENDIX C. STATUTE OF THE ARGENTINE REVOLUTION -- APPENDIX D. VENEZUELA: AGRARIAN REFORM LAW (1960) (excerpts) -- INDEX
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 23. Apr 2021).
JSTOR
Keywords: Law -- Latin America -- Cases; Law -- Latin America -- Cases; Droit -- Amérique latine -- Jurisprudence; NON-CLASSIFIABLE.; Law; Latin America; Trials, litigation, etc